PERBEDAAN KOMITMEN ORGANISASI DITINJAU DARI GENDER PEGAWAI DINAS PEMBERDAYAAN PEREMPUAN,PERLINDUNGA DAN PEMBERDAYAAN MASYARAKAT KATA TANJUNGPINANG - evita sandra (STIE PEMBANGUNAN TANJUNGPINANG, 2020)
This study aims to analyze differences in organizational commitment in advancing from gender in the women's empowerment, child protection and community empowerment services using quantitative research. From the results of data analysis using the Independent Sample T Test, it was found that there were differences in organizational commitment between employees with male sex and employees with female sex with a difference of 0.247 and Sig. (2- tailed) of 0.017 or 1.7% which is smaller than 0.05 or 5%. Which means that there are significant differences in the level of organizational commitment of employees with male sex compared to employees with female gender. And based on the results of a descriptive analysis of the variables obtained overall organizational commitment of employees with sufficient results. Keywords: organizational commitment, gender, employee